Análise técnica de um sistema de captura de movimentos integrado com um software de modelagem e simulação humana - Santos, William Rodrigues dos (2014)
The Motion Capture technology is considered a potential to overcome the limitations of traditional human simulation, reducing the time spent on creating and assigning greater reality simulations the simulated movements. This research presents an analysis of a technical system, formed by integrating a Motion Capture System with a human model and simulation software, aiming to establish ways to use the system in project process, contextualized by ergonomics. Different configurations of the main steps of the integration of the Motion Capture System Moven (Xsens), integrated with CAD DELMIA (Dassault Systèmes) software, which has a module of human simulation (Human Builder), through four experimental tests. Four trials were defined with factorial design to test the combination of different possible system configurations: i) spatial positioning of virtual environments, ii) mitigation of drift, iii) digital human kinematics and iv) anthropometric compatibility. From the results obtained in each test operating procedures were constructed in order to solve the problems and limitations of using these integrated technologies. The following procedures show how to configure the integrated system for positioning a virtual environment in a CAD system known coordinates, which enables the correction of the position due to drift of the capture system. Procedures that relate to the possible interactions between the body and capture the workplace, with the characteristics of the activity and the objectives of the simulation were also created. In addition, it was elaborated a systematic iterative to match the anthropometry between real human being, avatar of the capture system and digital human. The development of ways to use these technologies provides improvement of techniques used to construct the simulation, contributing to integration the perspective of future activity in the design in the design of productive situations.